Nilai-Nilai Spritualitas dan Harmoni Beragama dalam Wirid Harian Kitab Al-Aurad Al-Nur'aniyyah - Abdul Fadhil (Universitas Negeri Jakarta, 2018)
This research is based on religious issues that are stuck to the practice of normative zhahiriyah. Whereas the religious perfection lies precisely in the balance in practicing the religious zhahiriyah and bathiniyyah. In the religious teachings that bathiniyyah can actually grow and develop religious spirituality. Wirid Al-Aurad Al-Nur'aniyyah taught by tariqat al-Syadziliyyah containing readings is assumed to foster spiriualitas, harmony of religious behavior, not monolithic and tolerant. For this reason this study aims to describe and analyze the religious arguments about wirid. Then describe and analyze the texts, meanings, and interpretations of wirid Al-Aurad Al-Nur'aniyyah. Finally, analyze the relevance of such wirid practice in developing religious spirituality. This research uses qualitative research approach with descriptive research method and literature study. Descriptive method and literature study is used to describe the study of tasawuf and wirid in religious perspective. Then describes the data concerning wirid Al-Aurad Al-Nur'aniyyah, translating, and interpreting the meaning of wirid readings, and analyzing their relevance to the development of religious spirituality. The results showed that the daily wird of Al-Aurad Al-Nur'aniyyah readings such as al-Fatihah, al-Waqi'ah, shalawat, tahlil, tahmid, etc. as tariqat al-Syadziliyyah founder contained the meaning meaningful and relevant in developing religious spirituality. Wirid also as one effort in shaping the character of Islamic spirituality (Sufism). The wird that includes some form of remembrance and prayer contains an invitation to create harmony of life, pray for salvation and prosperity for all humanity regardless of religion and religious school.